Sulfur-Doped g-C3N4 with Enhanced Visible-Light Photocatalytic Activity - An Tran Doan; Phuc Nguyen Van; Tri Nguyen Ngoc; Phu Huynh Thi; Hung Nguyen Phi; Vien Vo (My University, 2019)
Sulfur-Doped g-C3N4 with Enhanced Visible-Light Photocatalytic Activity
Keywords: Sulfur-Doped g-C3N4; Photocatalytic; Visible-Light